3-Pyridinylboronic acid normalizes the effects of 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine exposure in zebrafish embryos - ALTURFAN, EBRU IŞIK; MEGA TİBER, PINAR (TAYLOR & FRANCIS LTD, 2022)
1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that damages dopaminergic neurons. Zebrafish has been shown to be a suitable model organism to investigate the molecular pathways in the pathogenesis of Parkinson's disease and also for potential therapeutic agent research. Boron has been shown to play an important role in the neural activity of the brain. Boronic acids are used in combinatorial approaches in drug design and discovery. The effect of 3-pyridinylboronic acid which is an important sub-class of heterocyclic boronic acids has not been evaluated in case of MPTP exposure in zebrafish embryos. Accordingly, this study was designed to investigate the effects of 3-pyridinylboronic acid on MPTP exposed zebrafish embryos focusing on the molecular pathways related to neurodegeneration and apoptosis by RT-PCR. Zebrafish embryos were exposed to MPTP (800 mu M); MPTP + Low Dose 3-Pyridinylboronic acid (50 mu M) (MPTP + LB) and MPTP + High Dose 3-Pyridinylboronic acid (100 mu M) (MPTP + HB) in well plates for 72 hours post fertilization. Results of our study showed that MPTP induced a P53 dependent and Bax mediated apoptosis in zebrafish embryos and 3-pyridinylboronic acid restored the locomotor activity and gene expressions related to mitochondrial dysfunction and oxidative stress due to the deleterious effects of MPTP, in a dose-dependent manner.
Keywords: 1-methyl-4-phenyl-1; 2; 3; 6-tetrahydropyridine; 3-pyridinylboronic acid; zebrafish embryo; neurodegeneration; apoptosis; PARKINSONS-DISEASE; BORONIC ACIDS; MPTP; IDENTIFICATION; ACTIVATION; APOPTOSIS; CASPASE-3; PERMEABILIZATION; DISRUPTION; ANTICANCER